DATA AND STATISTICS REQUIRED FOR HEATH PLANNINGS - GR Pezeshkian; F Amini (Tehran University of Medical Sciences, 1971)
Collecting and analyzing health related data and statistics are parts of health planning and in cases that lack sufficient data, the planning section is responsible for gathering the required information, by specific methods or carrying out research programs. In correct health planning, data collection and use of statistics and information, is not considered necessary in a large scale, but only required for as long as they have no objection with the aim of the planning and can be used in specific regional conditions. Since, planning is carried out with the health needs of a given population; the first step in data collection is related to the population. The second important group of data collection and vital statistics is related to the status of the epidemics, vital statistics, important and major health problems, environmental health, nutrition and expectancy, for diagnosing the community health. The third group of data collection and statistics are related to the health sources, manpower and the way the related institutions are active and managed. Finally, collecting helpful data, in the limits of possibilities in the health budget and expenses.